Analysis of lithofacies cyclicity in the Miocene Coal Complex of the Bełchatów lignite deposit, south-central Poland - Mastej, Wojciech; Bartuś, Tomasz; Rydlewski, Jerzy (Geologos, 2015)
Markov chain analysis was applied to studies of cyclic sedimentation in the Coal Complex of the Bełchatów mining field (part of the Bełchatów lignite deposit). The majority of ambiguous results of statistical testing that were caused by weak, statistically undetectable advantage of either cyclicity over environmental barriers or vice versa, could be explained if only the above-mentioned advantages appeared in the neighbourhood. Therefore, in order to enhance the credibility of statistical tests, a new approach is proposed here in that matrices of observed transition numbers from different boreholes should be added to increase statistical reliability if they originated in a homogeneous area. A second new approach, which consists of revealing statistically undetectable cyclicity of lithofacies alternations, is proposed as well. All data were derived from the mining data base in which differentiation between lithology and sedimentary environments was rather weak. For this reason, the methodological proposals are much more important than details of the sedimentation model in the present paper. Nevertheless, they did reveal some interesting phenomena which may prove important in the reconstruction of peat/lignite environmental conditions. First of all, the presence of cyclicity in the sedimentation model, i.e., cyclic alternation of channel and overbank deposits, represents a fluvial environment. It was also confirmed that the lacustrine subenvironment was cut off from a supply of clastic material by various types of mire barriers. Additionally, our analysis revealed new facts: (i) these barriers also existed between lakes in which either carbonate or clay sedimentation predominated; (ii) there was no barrier between rivers and lakes in which clay sedimentation predominated; (iii) barriers were less efficient in alluvial fan areas but were perfectly tight in regions of phytogenic or carbonate sedimentation; (iv) groundwater, rather than surface flow, was the main source of CaCO3 in lakes in which carbonate sedimentation predominated; (v) a lack of cyclic alternation between abandoned channels and pools with clayey sedimentation; (vi) strong evidence for autocyclic alternation of phytogenic subenvironments and lakes in which carbonate sedimentation predominated was found in almost all areas studied.